Robust path control for an autonomous ground vehicle in rough terrain. (May 2020) - Shin, Jongho; Kwak, Dongjun; Lee, Taehyung
Abstract: Typically, it is not trivial for an autonomous ground vehicle (AGV) to navigate in rough terrain due to lots of unexpectable uncertainties. Because the performance of the autonomous navigation can be degraded by the uncertainties, the AGV requires a robust control system against them. To handle the necessity, this study proposes the robust path controller by utilizing a disturbance observer (DOB)-based control method. The proposed controller is developed by two steps: the first step is to design a controller for handling a nominal system of the AGV, and the other is to add the DOB to the nominal controller. Then, the determined control input is distributed into tire forces because the tire forces are final resource enabling the AGV to move. The tire force distribution is defined as an optimization problem with some constraints, and the solution is obtained by the CVXGEN. Finally, numerical simulations and field tests with a skid-type ground vehicle, developed by the authors' laboratory, are conducted to validate the performance of the proposed method. Highlights: The integrated path control law for the skid-type ground vehicle is proposed using the DOB-based nonlinear control method. The stability of the proposed controller is thoroughly analyzed using the Lyapunov stability theory. The proposed method was validated using numerical simulations and field tests in the rough terrain.